Intimacy of married couples: Study on communication through WhatsApp - Nurhayati, Siti Rohmah; Prasetyo, Juni Nanda; Ndayambaje, Edmond (Psychological Research and Intervention, 2022)
This study aimed to find out the relationship between intimacy married couple and their communication via WhatsApp. This quantitative research with correlational method determines the correlation between two variables. The participants in this study amounted to 79 people who has been married for 5 years and using WhatsApp as a medium to communicate with their partner. The data collected using intimacy scale for married couple and a WhatsApp communication scale. Based on the results of the analysis using Product Moment correlation technique and simple linear regression analysis, this study revealed that the correlation coefficient between the intimacy of married couple and WhatsApp communication is 0,782 with a significance of 0,000. Communication via WhatsApp application contributed 27,9% toward intimacy married couple. Therefore, it can be concluded that communication via WhatsApp application can affect intimacy married couple.